Borrow and Adjust: Fiscal Policy and Sectoral Adjustment in an Open Economy - Erling Steigum; Øystein Thøgersen (Center for Economic Studies and ifo Institute (CESifo), 2001)
Should the government run fiscal deficits in response to an adverse external shock that warrants transfer of resources from production of non-traded to traded goods? This paper considers normative fiscal policy implications of sectoral adjustment costs in a two-sector model with overlapping generations. Fiscal deficits benefit present generations by depleting foreign assets and slowing down the adjustment process. We show that despite no nominal rigidities, temporary fiscal deficits increase social welfare if adjustment costs prevent immediate sectoral reallocation of inputs. If there are no adjustment costs, the case for fiscal deficits vanishes.
Keywords: 330; fiscal policy; sectoral adjustment; intergenerational welfare